The Łódź School of Econometrics: Institute of Econometrics - Górajski, Mariusz; Kębłowski, Piotr; Świeczewska, Iwona; Ulrichs, Magdalena; Welfe, Aleksander (Scientific Schools and Research Directions at the Faculty of Economics and Sociology, University of Łódź: The Present and the Future, 2025)
The chapter presents the history and contemporary profile of the Institute of Econometrics at the Faculty of Economics and Sociology, University of Łódź. The authors discuss its research and teaching traditions, focusing particularly on the last decade.